Interventional treatment of basilar trunk artery aneurysms associated with situs inversus totalis: A case report - Long, Tianlin; Xu, Quanhua; Chen, Xu; Ma, Yan; He, Yuanjian; Rao, Jia (Frontiers in Surgery, 2022)
Bsailar trunk aneurysm (BTAA) has an overall low incidence in intracranial aneurysm, but rupture is associated with a high morbidity and mortality in older people. Situs inversus totalis (SIT) is a rare congenital abnormality characterized by visceral rotation and vascular abnormalities. It has been described with several uncommonly clinical cases along with middle cerebral artery aneurysm and large carotid cavernous aneurysm. But the association between interventional embolization for BTAA association with SIT has not been reported. We describe the angiography findings and interventional treatment of one of the first of the association of BTAA with SIT.